APLIKASI DATA CENTER SYSTEM (DCS) BERBASIS CLOUD COMPUTING: Data Center System, Applications, Cloud, Computing, - Puad, Lailyn; Limia Budiarti, Rike (JURNAL AKADEMIKA, 2019)
The development of the digital world has increasingly created new spaces for researchers to deepen their knowledge and create new things. This is comparable to the challenges that were born to be conquered with the latest innovations. The digital world is closely related to data attachment. Data is a very vital need today. Many companies are aware of the importance of data willing to spend fantastic funds to produce a set of data. Of course this requires a large space to be utilized as much as possible. This research offers a solution that can be used to utilize a system in a structured, large scale and long term manner. This research produces an application that can be used by the campus in organizing documents on a large scale to facilitate anyone in accessing them. It is expected that this application can increase the awareness of all parties about the importance of archiving documents in digital form.